Coarse clast ridge sequences as suitable archives for past storm events?: Case study on the Houtman Abrolhos, Western Australia - Scheffers, A.; Scheffers, S.; Kelletat, D.; Squire, P.; Collins, Lindsay; Feng, Y.; Zhao, J.; Joannes-Boyau, R.; May, S.; Schellmann, G.; Freeman, H. (John Wiley & Sons, 2012)
Prehistoric storm records are relatively scarce in most parts of the world. This article presents stormrecords derived from coral rubble-based geological archives of the Houtman Abrolhos Archipelago located off the west coast of Australia, where the southernmost coral reefs of the Indian Ocean are found. Winter storm swell from the circum-Antarctic ‘Brave Westerlies’, as well as tropical cyclone waves, have left numerous ridge systems on dozens of islands of the archipelago, all composed of coral rubble from adjacent reefs. At three islands, seven ridge systems were dated by three different methods: U-series (68 dates), radiocarbon (64 dates), electron spin resonance (7 dates); 139radiometric dates span the last 5500 years of the Holocene. In contrast to the geomorphological interpretation, the age sequences show ‘inversions’, hiatuses and different ages for the same ridge, all pointing to complicated ridge formation processes. Time gaps, some exceeding 1000 years, are interpreted as phases of erosion and not as phases without storm activity.